2015
DOI: 10.1002/pbc.25570
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of bronchoalveolar lavage and respiratory tract biopsies in diagnosis and management of suspected invasive respiratory fungal infections in children

Abstract: BAL and biopsy in children with an oncological diagnosis or those undergoing HSCT only infrequently lead to changes in management in the era of empiric therapy with broad-spectrum anti-fungal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Our study supports the observations made in prior series that a positive result from BAL impacts treatment decisions . We found that most negative BALs were associated with discontinuing at least one non‐targeted antimicrobial, although often another non‐targeted agent was continued.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study supports the observations made in prior series that a positive result from BAL impacts treatment decisions . We found that most negative BALs were associated with discontinuing at least one non‐targeted antimicrobial, although often another non‐targeted agent was continued.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, negative BALs may have reflected non‐infectious causes of lower tract disease such as graft‐versus‐host disease or pulmonary fibrosis, as has been previously described . Recent comparison studies have suggested that lung biopsy may elucidate noninfectious diagnoses in a manner superior to that of BAL, though this procedure is associated with higher morbidity and mortality than BAL.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, our study demonstrates that the costs related to diagnosis and initial management of RT‐IFI in pediatric oncology and HSCT patients are significantly higher when patients undergo an invasive diagnostic procedure. Combined with our previous data that BAL and RTB only infrequently (8%–13% of the time) lead to a change in management in this population in the era of empiric broad‐spectrum antifungal therapy and advanced imaging techniques, the significantly higher morbidity and costs make these invasive diagnostic techniques less attractive. Currently utilized noninvasive diagnostic methods include testing for galactomannan, a cell wall component of aspergillus species, and 1,3‐β‐ d ‐glucan, a major cell wall component of most fungal species except zygomycetes and cryptococcus species, which can both provide supportive evidence of RT‐IFI, but have inadequate sensitivity/specificity and are lacking in information on speciation and antifungal susceptibilities .…”
Section: Discussionmentioning
confidence: 89%
“…A review of the electronic medical record revealed 119 oncology or post‐HSCT patients at our institution who were suspected of have RT‐IFI between 2007 and 2012. Eighteen of these patients were excluded from this study and our previous study because their fungal infection did not involve the respiratory tract. Twenty‐five patients were excluded from the current study due to insufficient cost data available in our database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation